Bitcoin Versus Electronic Money - Rotman, Sarah (World Bank, Washington, DC, 2014)
Bitcoin has had a volatile journey since it was launched in 2009, attracting attention among conventional investors as well as the black market. Regulators and policy makers are also following Bitcoin, raising the occasional eyebrow as they evaluate Bitcoin's risks and benefits and how to regulate this little understood virtual currency. Some media reports have confused Bitcoin with more popular electronic money (e-money) schemes used in many low-income countries to reach the unbanked. But the two are markedly different and should not be conflated. This brief provides information about Bitcoin and contrasts Bitcoin with e-money to avoid alarm about the former to the detriment of the latter.